PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PREZI PADA MATERI RUMUS JUMLAH DAN SELISIH DUA SUDUT TRIGONOMETRI UNTUK KELAS XI SMA - Wafiatul Lutfiah; Darsono Darsono; Bambang Agus Sulistyono (UNEJ e-Proceeding, 2022)
This research was motivated by observations made by researchers. Students had difficulty memorizing the formula for the sum and difference of two trigonometric angles. And the use of textbooks is less attractive for students to read. Therefore, the researchers developed Prezi-based learning media to solve these problems. The purpose of this study was to determine the steps for developing Prezi-based learning media and to determine student responses to the use of Prezi-based learning media on the formula for the sum and difference of two trigonometric angles for class XI SMA during the learning process. This study uses the ADDIE model's research and development (R&D) methods (Analysis, Design, Develop, Implement, Evaluate). The subjects of this study were students of class XI. They collected data by distributing questionnaires for student responses to the limited and expansion tests. Based on the research objectives with the stages of the ADDIE development model, it has been obtained based on learning media. And student responses based on the results of the limited test and the expansion test received relatively good and reasonable answers. Keywords: Development of learning media, Prezi, Trigonometry